2023
DOI: 10.3390/min13040559
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Sulfate Crystallization in Presence of Fluorecent-Tagged Polyacrylate and Some Refinement of Scale Inhibition Mechanism

Abstract: Deposits of calcium sulfate scale on the surfaces of industrial equipment in distillation facilities, reverse osmosis desalination plants, in oil and gas industries lead to significant clogging of pipes and membranes and to a serious increase in production costs. For the mitigation of scale formation, the wide spectrum of antiscalants is applied. The present work is dedicated to the study of calcium sulfate deposition from supersaturated aqueous solutions in the presence of polyacrylic antiscalant with fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…The fluorophore fragment represents 0.5% of the total mass of the PAA-F1 molecule, as shown in Figure 2. It was observed that PAA-F1 functions as an effective antiscalant for gypsum [16] and is superior to PAA due to its ability to be monitored by fluorimetry for concentration measurement.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The fluorophore fragment represents 0.5% of the total mass of the PAA-F1 molecule, as shown in Figure 2. It was observed that PAA-F1 functions as an effective antiscalant for gypsum [16] and is superior to PAA due to its ability to be monitored by fluorimetry for concentration measurement.…”
Section: Methodsmentioning
confidence: 99%
“…The corresponding data are shown in Table 1. Our previous research [16] has revealed the unavoidable presence of a smaller particle fraction (1 nm ≤ size ≤ 100 nm), with concentrations reaching at least 10 7 units per 1 mL. Consequently, these nano/micro-impurities might act as crystal formation centers for gypsum.…”
Section: The Blank Experimentsmentioning
confidence: 98%
See 2 more Smart Citations
“…The reported small reduction in the nucleation rate for isonicotinamide crystallization from ethanol after removing particles with sizes > 0.45 µm [53] appears to be consistent with this proposition. It has also been reported that nano-sized (diameters ~1 nm) impurities are likely present in solutions with extremely high number densities [63], but these impurities would likewise not remove the need for assembling the complex transition state. They may perhaps appear as inclusions in nuclei formed in their neighborhood (note also that 1 nm is of a similar size as the reversible aggregate sizes).…”
Section: Homogeneous Vs Heterogeneous Nucleationmentioning
confidence: 99%